Comparison of two surgical techniques in the treatment of multiple gingival recessions sandwiched with a combination of A-PRF and L-PRF - Shaik Sameera; Medandrao Nagasri; Pavuluri Aravind Kumar; Pantareddy Indeevar; Kalapala Raviraj; S.V.V.S. Musalaiah (Elsevier, 2018)
Aim: The aim of this study is to compare semilunar vestibular incision technique with pouch and tunnel technique in combination with A-PRF and L-PRF for treatment of Miller's class I and II multiple gingival recessions. Method: This is a randomized, controlled, double-blinded, split mouth study which consists of 16 systemically healthy patients with 96 sites and a mean age of 34.2 years, and divided randomly into 2 groups, Group A consists of semilunar vestibular incision technique sandwiched with A-PRF and L-PRF and Group B consists of Pouch and tunnel technique sandwiched with A-PRF and L-PRF. Clinical parameters were recorded at baseline, 3 months and 6 months which include plaque index, gingival index, recession depth, recession width, clinical attachment loss and width of keratinized tissue. Results: All the clinical parameters showed significantly better levels for both the groups from baseline to 6 months. Semilunar vestibular incision technique showed greater significance when compared to pouch and tunnel technique from baseline to 6 months post operatively. Conclusion: The combination of A-PRF and L-PRF with pouch and tunnel technique and semilunar vestibular technique showed better outcome 6 months post operatively. Semilunar vestibular incision technique showed promising results than pouch and tunnel technique for the treatment of multiple gingival recessions. Keywords: Gingival recession, Semilunar vestibular incision technique, Pouch and tunnel technique, A-PRF, L-PRF